Challenges and problems of petrochemical companies’ use of secondary resources - T. M. Gainochenko; M. V. Gainochenko (Управление)
The environmental agenda for the development of economic systems necessitates the formation of a market for secondary petrochemical products. A comparative analysis of the policies of sustainable development of petrochemical companies showed that the policy of sustainable development of individual budinesses is currently focused on the use of the following tools: development of the product portfolio, participation in international initiatives, partnerships and forums; voluntary industry initiatives and private projects to implement the first steps towards the collective goals of sustainable development. Among the main solutions of the reviewed organisations are products made of renewable raw materials and recyclable products. At the same time, the implementation of the responsible production and consumption by petrochemical companies is limited by the production and technological solutions of manufacturers of consumer goods. Environmentally unsustainable use of polymers by such enterprises makes their recycling difficult and limits the implementation of the concept of circular economy in petrochemicals. The article identifies key problems in the management and use of secondary resources: underdeveloped waste market conditions; uneven scale and geography of waste; inconsistent and inefficient (unsystematic) measures of waste market regulation, difficulties in forecasting prices for key raw materials and building a pricing mechanism in key markets, which are represented by polyethylene terephthalates, high density polyethylene, low density polyethylene and polypropylene. The introduction of chemolysis into the well-established technological processes of oil and gas chemical companies to work with secondary polymers requires an assessment of the acceptable level of risk. The needs of the market on the part of customers are not fully formed, so the dynamic changes, creating difficulties for petrochemical companies. Most of the highlighted problems are typical for both Russian and global markets of secondary petrochemicals. At the same time, the features of state regulation and logistics services for secondary petrochemical products are regional in nature, therefore, they are considered in the work for the conditions of the Russian Federation.